GSA-based optimal backstepping controller with a fuzzy compensator for robust control of an autonomous quadrotor UAV - Mohd. Basri, Mohd. Ariffanan (Emerald Group Publishing, 2015)
Purpose-The purpose of this paper is to propose a new approach for robust control of an autonomous quadrotor unmanned aerial vehicle (UAV) in automatic take-off, hovering and landing mission and also to improve the stabilizing performance of the quadrotor with inherent time-varying disturbance. Design/methodology/approach-First, the dynamic model of the aerial vehicle is mathematically formulated. Then, a combination of a nonlinear backstepping scheme with the intelligent fuzzy system as a new key idea to generate a robust controller is designed for the stabilization and altitude tracking of the vehicle. For the problem of determining the backstepping control parameters, a new heuristic algorithm, namely, Gravitational Search Algorithm has been used. Findings-The control law design utilizes the backstepping control methodology that uses Lyapunov function which can guarantee the stability of the nominal model system, whereas the intelligent system is used as a compensator to attenuate the effects caused by external disturbances. Simulation results demonstrate that the proposed control scheme can achieve favorable control performances for automatic take-off, hovering and landing mission of quadrotor UAV even in the presence of unknown perturbations. Originality/value-This paper propose a new robust control design approach which incorporates the backstepping control with fuzzy system for quadrotor UAV with inherent time-varying disturbance. The originality of this work relies on the technique to compensate the disturbances acting on the quadrotor UAV. In this new approach, the fuzzy system is introduced as an auxiliary control effort to compensate the effect of disturbances. Because the proposed control technique has the capability of robustness against disturbance, thus, it is also suitable to be applied for a broad class of uncertain nonlinear systems